Applying CVaR for decentralized risk management of financial companies - Mulvey, John M.; Erkan, Hafize G. (Journal of Banking & Finance, 2006)
Over the past decade, financial companies have merged diverse areas including investment banking, insurance, retail banking, and trading operations. Despite this diversity, many global financial firms suffered severe losses during the recent recession. To reduce enterprise risks and increase profits, we apply a decentralized risk management strategy based on a stochastic optimization model. We extend the decentralized approach with the CVaR risk-metric, showing the advantages of CVaR over traditional risk measures such as value-at-risk. An example taken from the earthquake insurance area illustrates the concepts.